Mapping of functional domains of the lipid kinase phosphatidylinositol 4-kinase type III alpha involved in enzymatic activity and hepatitis C virus replication - Harak, Christian; Radujković, Danijela; Taveneau, Cyntia; Reiss, Simon; Klein, Rahel; Bressanelli, Stéphane; Lohmann, Volker (Journal of virology, 2014)
The lipid kinase phosphatidylinositol 4-kinase III alpha (PI4KIIIα) is an endoplasmic reticulum (ER)-resident enzyme that synthesizes phosphatidylinositol 4-phosphate (PI4P). PI4KIIIα is an essential host factor for hepatitis C virus (HCV) replication. Interaction with HCV nonstructural protein 5A (NS5A) leads to kinase activation and accumulation of PI4P at intracellular membranes. In this study, we investigated the structural requirements of PI4KIIIα in HCV replication and enzymatic activity. Therefore, we analyzed PI4KIIIα mutants for subcellular localization, reconstitution of HCV replication in PI4KIIIα knockdown cell lines, PI4P induction in HCV-positive cells, and lipid kinase activity in vitro. All mutants still interacted with NS5A and localized in a manner similar to that of the full-length enzyme, suggesting multiple regions of PI4KIIIα are involved in NS5A interaction and subcellular localization. Interestingly, the N-terminal 1,152 amino acids were dispensable for HCV replication, PI4P induction, and enzymatic function, whereas further N-terminal or C-terminal deletions were deleterious, thereby defining the minimal PI4KIIIα core enzyme at a size of ca. 108 kDa. Additional deletion of predicted functional motifs within the C-terminal half of PI4KIIIα also were detrimental for enzymatic activity and for the ability of PI4KIIIα to rescue HCV replication, with the exception of a proposed nuclear localization signal, suggesting that the entire C-terminal half of PI4KIIIα is involved in the formation of a minimal enzymatic core. This view was supported by structural modeling of the PI4KIIIα C terminus, suggesting a catalytic center formed by an N- and C-terminal lobe and an armadillo-fold motif, which is preceded by three distinct alpha-helical domains probably involved in regulation of enzymatic activity. - IMPORTANCE The lipid kinase PI4KIIIα is of central importance for cellular phosphatidylinositol metabolism and is a key host cell factor of hepatitis C virus replication. However, little is known so far about the structure of this 240-kDa protein and the functional importance of specific subdomains regarding lipid kinase activity and viral replication. This work focuses on the phenotypic analysis of distinct PI4KIIIα mutants in different biochemical and cell-based assays and develops a structural model of the C-terminal enzymatic core. The results shed light on the structural and functional requirements of enzymatic activity and the determinants required for HCV replication.
Gesehen am 16.09.2020